The Implementation of IAAF Kids Athletics in Elementary Schools: Can it Enhance the Student’s Motivation to Participate in Physical Education and Improve Their Physical Performance? - Blatsis, Πέτρος; Saraslanidis, Πλούταρχος; Barkoukis, Βασίλειος; Manou, Βασιλική; Tzavidas, Κωνσταντίνος; Hatzivasiliou, Χρήστος; Palla, Σταματία (Inquiries in Physical Education and Sport, 2015)
The purpose of this study was to implement the IAAF Kids Athletics (IAAF track and field teaching program) in an elementary school context (5th and 6th grade) and investigate the effect of the program on student’s motivation to participate in physical education, on their perceived enjoyment and effort, and their physical performance. The sample consisted of 226 students (101 boys and 125 girls). Their mean age was 11.42 years (.46). The IAAF Kids Athletics was implemented in an experimental group (106 students). The students of the control group (120 students) were taught physical education according to the instructions given by the Greek curricular for elementary schools. The intervention lasted for twelve weeks. The perceived Locus of Causality, the perceived enjoyment and effort subscales of the Intrinsic Motivation Inventory, were administered to the students, prior to and after the intervention. Pre and post-experimental physical performance measurements were conducted. Split plot ANOVAs were used to estimate the time and group interaction effects on each variable. The results showed that the program helped students to improve their identified regulation and their perceived effort, more than regular physical education. The same positive results were revealed for most physical performance variables. As a conclusion, the IAAF Kids Athletics can help students to increase their effort and finally become more motivated in Physical Education, by developing a more self-determined type of motivation, as well as to improve their physical performance.